CIHEULANG RIVER FLOOD ANALYSIS IN CARINGIN DISTRICT SUKABUMI REGENCY - Yulia A; Utamy Sukmayu Saputri; Triono; Kornienko Elena Vladimirovna (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2020)
This study aims to study and analyze the intensity of rainfall, flood discharge and flood control of the Ciheulang River in Caringin District, Sukabumi Regency. The method used is a statistical and empirical model analysis approach including the distribution of Log Pearson Type III, Intensity Duration Frequency and rational methods. Based on the results of the study, it is known that (1) The intensity of rainfall in the Ciheulang river in Caringin District, Sukabumi Regency in a 2 year period is 7.999 mm/second, a 5 year period 9, 215 mm/second, a 10 year period 9,922 mm/second, a 25 year period 10,736 mm/second, period of 50 years 11.297 mm/second and period of 100 years 11.825 mm/second; (2) Ciheulang river flood discharge in Caringin District, Sukabumi Regency for a 2 year period is 38.424 mm/second, a 5 year period 44,266 mm/second, a 10 year period 47,664 mm/second, a 25 year period 51.574 mm/second, a 50 year period 54.269 mm/second and period of 100 years 56,807 mm/second; (3) Control of flooding that occurred in the Ciheulang river in Caringin District, Sukabumi Regency is carried out by reducing and overcoming runoff that occurs due to planned flood discharges with various return periods, through alternative structural efforts, including: making/raising flood embankments using revetments, gabions river channel.